2020
DOI: 10.1039/d0ma00097c
|View full text |Cite
|
Sign up to set email alerts
|

Melamine adsorption on carbon materials: impact of carbon texture and surface chemistry

Abstract: In this work, a comparative study between three carbon materials has been carried out to investigate the impact of the micro/mesoporous structure of the carbon substrate on their adsorption capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Since Mel is characterized as a weak base, it may form protonated species in mild acid electrolytes. 25 The pH of ZnSO 4 and Mel/ZnSO 4 electrolytes is rst determined using a digital pH meter. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Mel is characterized as a weak base, it may form protonated species in mild acid electrolytes. 25 The pH of ZnSO 4 and Mel/ZnSO 4 electrolytes is rst determined using a digital pH meter. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1b). 25 Therefore, it is concluded that Mel tends to form MelH + by coordinating with protons (H + ) in the Mel/ZnSO 4 electrolyte. It should be pointed out that since the coordination capability of Mel is inferior to that of NH 3 that cannot coordinate with Zn 2+ in weak acid solutions, the formation of the Zn 2+ -Mel complex is impossible in ZnSO 4 electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…The MF copolymer consists of 1,3,5-triazine, a flexible third amine and ether groups frequently used as an additive of separators, a N-doping reagent of active materials, and a cross-linker for mechanical maintenance of the composites. For LIB applications, the thermal stabilities and cross-linking properties of MF copolymers are advantageous for preventing the elution of active materials and slurry inhomogeneity. Moreover, the 1,3,5-triazine backbones in the MF copolymer enable intensive interaction with CNTs, effectively restricting CNT folding. , Owing to the increased surface area of the well-dispersed CNTs that results from the inclusion of MF copolymers, HNBR-mediated gelation is restricted because of the loosened cross-linking of HNBR. In addition, the MF copolymer-mediated individualization of the CNTs affects their slurry dispersion during the general mixing process of the active materials, conductive carbon, the binder, and the melamine additive.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, the 1,3,5-triazine backbones in the MF copolymer enable intensive interaction with CNTs, effectively restricting CNT folding. 41,42 Owing to the increased surface area of the well-dispersed CNTs that results from the inclusion of MF copolymers, HNBR-mediated gelation is restricted because of the loosened cross-linking of HNBR. In addition, the MF copolymer-mediated individualization of the CNTs affects their slurry dispersion during the general mixing process of the active materials, conductive carbon, the binder, and the melamine additive.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The study on LPE of BP with the aqueous solution is rarely conducted; moreover, it should be considered as how to effectively obtain as-exfoliated BP nanosheets with the issue regarding residual dispersants. , Thus, developing LPE of BP in an aqueous solution and further extraction of BP nanosheets is crucial for the versatile applications. Melamine-assisted LPE of graphene showed superior enhancement with high-yield and larger crystallite production due to the presence of hydrophilic NH 2 groups and π–π interaction between graphene and melamine. Additionally, the as-exfoliated graphene is in situ encapsulated by melamine molecules which prevent oxidation of the graphene from acid species but can be easily washed away by water due to the high solubility of melamine nevertheless . Therefore, the strategy in this study for LPE of BP is using melamine in aqueous solution to obtain high-quality BP nanosheets.…”
Section: Introductionmentioning
confidence: 99%